Resorufin as a New Redox Indicator in the Determination of Copper(II) with Iron(II) - Vijayaraju, K.; Rambabu, T. (Asian Journal of Chemistry, 2013)
A simple accurate and convenient reductimetric titration method has been developed for the determination of copper(II) using iron(II) as a reductimetric reagent and employing resorufin as an advantageous redox indicator. The method consists in titrating copper(II) with iron(II) in 7-8 M phosphoric acid medium and in presence of 1.8 M bromide or 2.0 M chloride ions using resorufin as a redox indicator. The colour transition of the indicator at the end-point (red to green) is sharp and reversible and no indicator correction need to be applied. Copper(II) in the range 10-30 mg has been determined with an accuracy of ± 0.6 %. The precession of the method has been determined by computing the pooled standard deviation and 95 % confidence limits. The method developed has been extended for the determination of copper content in a sample of brass. The formal redox potentials of [copper(II)]/[copper(I)] couple or oxidant system and those of [iron(III)]/[iron(II)] couple or reductant system have been measured under the above mentioned optimum titration conditions and explained the conditions needed in the titration. The role of chloride and bromide ions has been briefly discussed. The transition potential of the indicator resorufin has been measured and explained its suitability as a redox indicator in the method. The interferences due to diverse ions have also been studied.